Investigation and optimization of solar volumetric absorption systems using nanoparticles - Bonab, H. Bashirpour; Javani, N. (ELSEVIER, 2019)
In the current study, a numerical modelling for the thermal performance of a solar collector is improved. In order to enhance the heat transfer rate, three types of nanofluids, including copper oxide, aluminum oxide and carbon nanotubes are studied where the base fluid is the water. Thermal performance and temperature distribution in the solar collector pipelines are investigated by changing nanoparticles and their volumetric concentration. The applied volumetric fractions are 1%, 3%, 5%, 7% and 10%. Results indicate that the thermal performance of the absorbing pipe is improved compared to the pure water. Furthermore, carbon nanotubes show a better heat transfer behavior compared to other nanoparticles. For volumetric fractions less than 5%, the system shows better efficiency compared with higher volumetric fractions.
Keywords: Solar water heater; Nanofluid; Solar energy; Solar collector; Volumetric fraction; ENHANCED THERMAL-CONDUCTIVITY; HEAT-TRANSFER; ENERGY; NANOFLUIDS; SUSPENSIONS; COLLECTORS; Energy & Fuels; Materials Science; Physics